Roads and Railway Lines in Serbia after the Balkan Wars - Jagodić, Miloš (European Journal of Multidisciplinary Studies, 2016)
This paper deals with Kingdom of Serbia’s plans on roads and railways construction in the regions annexed 1913, after the Balkan Wars. Plans are presented in detail, as well as achievements until 1915, when the country was occupied by enemy forces in the World War One. It is shown that plans for future roads and railways network were made according to the changed geopolitical conditions in the Balkan Peninsula, created as the consequence of the Balkan Wars 1912-1913. The paper draws mainly on unpublished archival sources of Serbian origin.